Overcoming "The Valley of Death". (1st September 2014) - McIntyre, Robin.
On a global level there are major challenges arising from climate change, resource use and changing age demographics. These issues have created a global marketplace for novel innovative products and solutions which can help to combat and overcome these challenges which have created significant commercial opportunities for companies, particularly for small and medium size enterprises or SMEs. Companies most likely to take advantage of these opportunities will be those which can innovate in a timely manner. Innovation significantly contributes to higher productivity and economic growth, and is core to a company's competitiveness within often challenging marketplaces. However, many factors can stifle innovation. Companies can struggle to identify finance for early-stage development, the returns can be difficult to predict, and the innovation 'landscape' is often complex and unclear. This brief review describes some of the main issues with commercialising innovative ideas and provides guidance with respect to the often complicated funding landscape both on a National and European level.